1997
DOI: 10.1136/adc.76.5.445
|View full text |Cite
|
Sign up to set email alerts
|

Continuous midazolam infusion as treatment of status epilepticus

Abstract: In a tertiary referral centre, midazolam infusion was tried as treatment for 20 children with status epilepticus over a period of two years. The mean age of the children was 4.07 years. Twelve children with refractory status epilepticus had received intravenous or per rectal diazepam and intravenous phenytoin/ phenobarbitone or both before midazolam was given (0.15 mg/kg bolus followed by 1-5 µg/kg/min infusion). Eight children required only midazolam to control the established status epilepticus. The seizures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1
8

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 14 publications
(13 reference statements)
0
58
1
8
Order By: Relevance
“…Intravenous midazolam infusion has been shown to be effective in the most worrisome patients, those with refractory status epilepticus unresponsive to the usual anticonvulsants (diazepam, lorazepam, phenytoin, and phenobarbital) (8,(10)(11)(12)(13). Midazolam as a single dose, or as an infusion, is able to stop refractory status epilepticus effectively (8,(10)(11)(12)(13). If midazolam is proposed as the medication to use after all others have failed, it would seem logical that it could be a good choice as a first line agent as long as there are no adverse side effects to its use.…”
Section: Drug Management For Acute Tonic-clonic Convulsions Includingmentioning
confidence: 99%
“…Intravenous midazolam infusion has been shown to be effective in the most worrisome patients, those with refractory status epilepticus unresponsive to the usual anticonvulsants (diazepam, lorazepam, phenytoin, and phenobarbital) (8,(10)(11)(12)(13). Midazolam as a single dose, or as an infusion, is able to stop refractory status epilepticus effectively (8,(10)(11)(12)(13). If midazolam is proposed as the medication to use after all others have failed, it would seem logical that it could be a good choice as a first line agent as long as there are no adverse side effects to its use.…”
Section: Drug Management For Acute Tonic-clonic Convulsions Includingmentioning
confidence: 99%
“…Specifically, the results of the retrospective audit would support at least one previous study (Appleton et al 1995) in suggesting that a second dose of diazepam may not be effective and could therefore be omitted from the protocol. In addition, it may be more appropriate to compare diazepam with either lorazepam (Leppik et al 1983, Mitchell and Crawford 1990, Appleton et al 1995 or midazolam (McDonagh et al 1992, Rivera et al 1993, Lal Koul et al 1997, as recent evidence has suggested that these drugs may be as, or more, effective and safer than diazepam (Mitchell 1996, Pellock 1998. These issues are important as they facilitate the development of a definitive and paediatric 'evidence-based' protocol, rather than one based largely on anecdotal experience or from extrapolation of adult studies.…”
Section: Discussionmentioning
confidence: 99%
“…Midazolam (MDL) is a very rapidly acting BD with a short half-time [190,191]; therefore, stable antiepileptic effect needs repetitive or continuous administration [201][202][203]. It also has markedly sedative and stronger respiratory depressive properties which make it less suitable for first-line treatment of SE, but it is widely used for the treatment of refractory SE (RSE, cf.…”
Section: S C H W E I Z E R a R C H I V F ü R N E U R O L O G I E U N mentioning
confidence: 99%